The role of institutional pressure in driving carbon integration within the Southeast Asian industrial sector - Rahmawati, Yunaita (Advances in Accounting Innovation, 2025)
Objective: Specifically this study seeks to assess the effect of institutional pressure and legitimacy motivation on carbon intelligence integration (CII), and the moderating role of carbon governance maturity (CGM) in high and low carbon intensive industries.Methods: Explanatory approach quantitative manufacturing-energy sectors Southeast Asia regression moderation analysis robustness checks alternative dependent variables empirical validation.Results: The influence of carbon intelligence integration (CII) was highly and significantly influenced by institutional pressure and legitimacy motivation. This relationship was significantly strengthened by the moderating role of carbon governance maturity (CGM), especially at high governance quality levels. In terms of sectoral analysis, the positive impact of ESG performance on stock returns was stronger in the case of firms with lower carbon intensity as well as EPS was consistently found to be a reliable predictor of stock returns across sectors.Novelty: This study is first of its kind to assess the contextual determinants of the relationship between institutional pressure, legitimacy motivation and carbon intelligence integration by proposing and examining carbon governance maturity (CGM) as a potential moderator. Its unique approach is the cross-sectional comparison of high- and low-carbon sectors that sheds light on the contrasting behavioral effects of ESG and earnings variables under differing environmental and sectoral intensities.Research Implications: The results highlight the need to prioritize governance recommendations to better enable carbon intelligence. Sectorial and governance maturity-based ESG disclosure sub benchmarks should be used by policymakers and business leaders to harmonize ESG reporting standards, leading to improved capital market reactions, sustainability practices and long-term firm value. By focusing on transition economies where challenges for carbon disclosure are acute, the study provides evidence for differentiated ESG regulation.